Media Video Tutorial sebagai Inovasi Pembelajaran Pastry : Dampaknya terhadap Hasil Belajar Siswa di SMKN 1 Batusangkar (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to investigate the influence of video tutorial implementation as learning media on academic achievement of students in Pastry courses at SMK Negeri 1 Batusangkar. The study employed quantitative methodology utilizing a quasi-experimental approach with Nonequivalent Control Group Design. The entire population of grade XI Culinary students was categorized into experimental and control cohorts. Analysis findings revealed that experimental group participants demonstrated substantial improvement in posttest performance compared to their control group counterparts. T-test results indicated that educational video materials exerted beneficial effects on learners' academic capabilities. The statistical significance level from the t-test yielded 0.000, which falls beneath the 0.05 threshold. This instructional medium demonstrated efficacy in enhancing comprehension, self-directed learning, and academic motivation. Consequently, video-based tutorials represent an efficient pedagogical approach for practical instruction in vocational education institutions.